Short Communication: Identification and phylogenetic analysis of Corynebacterium diphtheriae isolates from Jakarta, Indonesia based on partial rpoB gene - Andi Yasmon; YEVA ROSANA; DONI USMAN; LUH INTA PRILANDARI; TEGUH SARRY HARTONO (Society for Indonesian Biodiversity, 2020)
Abstract. Yasmon A, Rosana Y, Usman D, Prilandari LI, Hartono TS. 2020. Short Communication: Identification and phylogenetic analysis of Corynebacterium diphtheriae isolates from Jakarta, Indonesia based on partial rpoB gene. Biodiversitas 21: 3070-3075. Indonesia is a developing country with the greatest potential of diphtheria, so accurate identification is needed to detect C. diphtheriae. The genetic relationship analysis is important to be determined so that this transmittable disease can be prevented. In this study, we reported the identification and phylogenetic analysis of C. diphtheriae based on partial rpoB gene. Twelve samples from throat swabs of diphtheria suspected patients from 2018 to 2019 were used in this study. The result of VITEK 2 ANC-Automated Testing identified that all isolates were C. diphtheriae. However, the identification based on partial rpoB gene analysis showed that only 10 out of 12 isolates were C. diphtheriae, while 2 other isolates were C. argentoratense. Of 10 C. diphtheriae strains/isolates, 2 strains were unique for Indonesia. Thus, it is needed to evaluate the accuracy of VITEK 2 ANC-Automated Testing and to conduct further comprehensive studies on the genetic relationships of C. diphtheriae strains based on multiple virulence genes, multilocus sequence typing and/or whole-genome analysis.